Pemberian Imbalan Via Aplikasi TikTok Perspektif Hukum Ekonomi Syariah: Analisis Terhadap Program TikTok Affiliate - Wahidin, Wahidin; Safaruddin, Safaruddin (Universitas Islam Negeri Sumatera Utara, 2024)
In daily life, one cannot escape from muamalah activities, whether to meet daily needs such as buying and selling, forming relationships such as marriage, or fulfilling emotional needs such as entertainment. The use of the TikTok application with the provision of commissions or rewards to someone for their actions is a modern example of muamalah. This person receives a certain amount of money or other forms of payment for specific work. The issues discussed in this research are What is the mechanism for giving rewards on the TikTok application and What is the view of Sharia economic law on giving rewards in the TikTok application? This research uses the library research method with documentation from the study of Syafi’i school books, works by classical and contemporary Syafi’iyah scholars, academic journals, institutional repositories, and related scientific articles as primary data sources. The research results show that: firstly The reward mechanism on TikTok Affiliate starts with the registration of creators who promote products through content containing links. A commission of 10-30% is given after a successful transaction and is recorded in the account dashboard, paid after reaching a certain amount. This mechanism ensures fairness and transparency in accordance with the principle of ju’alah contracts and provides additional income opportunities for creators. And secondly The TikTok Affiliate program is a form of muamalah, which is permissible as long as there is no evidence prohibiting it. However, this program can become haram if its practices do not comply with Islamic law.